Genotoxic and Histopathological Effects of Chlorpyrifos on African Catfish, C. gariepinus and Ameliorative Potentials of Ackee Apple, blighia sapida Seed - Iyiolai, Oluyinka; Adeagbo, A. A.; Weliange, W. S.; Abdulkareem, S. I.; Abbas, Anifowoshe T.; Belewu, M. A. (Science Journal of University of Zakho, 2018)
Chlorpyrifos (CPF) is a very toxic pesticide commonly used for controlling agriculturally important pests. The present study investigates DNA damaging effects of CPF on Clarias gariepinus was assessed using genetic assays. Fish were exposed to varying concentrations of CPF (100ppm, 200ppm and 300ppm) at 96 hours (acute exposure). LC50 of the pesticide was found to be 120ppm and one-tenth of the LC50 (12ppm) was taken for the chronic exposure. Distilled water and colchicine were used as negative and positive controls respectively. After 28 days of chronic exposure, fish were fed with inclusion of B. sapida seed (powder) for 14 days. Liver and gills of the fish were removed following 96h exposure, days 7, 14 and 28 of the chronic exposure as well as after the period of amelioration (14 days) for CA assay and histopathological analysis. The results of CA assay showed statistically significant (p ˂ 0.05) increase in CA in a dose-dependent manner for all the exposed groups after acute exposure and time dependent after chronic exposure. Also, this study showed that CPF can potentially induce genotoxic and histopathological changes in fish and other aquatic organisms.